Model of preemptive embedded systems for optimizing real-time performance - WEN Tao1; WANG Ji-yong2; WANG Xiao-xia1; ZOU Xiang1 (Tongxin xuebao)
By analyzing preemptions in embedded real-time systems adopting RM scheduling policy, created a preemption model of periodic real-time tasks. This model described the relationship between overheads incurred by preemptions and the properties of real-time tasks, such as priorities, periods, execution times, deadlines, release times etc. It also showed the relation between the schedulability of the task set and properties of its real-time tasks. Based on the model and taking the idea of parasitism in biology, this paper presented a method of optimizing real-time performance of the embedded systems under the RM scheduling mechanism. This method can reduce preemptions or change the relations of preemptions, decrease overheads to improve real-time performance by adjusting release times of tasks. And then the optimization method underlying the model is evaluated by experiments.